Réponses

2013-12-13T22:48:21+01:00
A=-6(2x-3)(5-4x)
A=-6[10x-8x²-15+12x]
A=-6[-8x²+22x-15]
A=48²-132x+90

B=(x-6)(-2x+1)(3x-4)
B=(x-6)[-6x²+11x-4]
B=-6x³+11x²-4x+36x²-66x+24
B=-6x³+46x²-70x+24

C=(x-2)(x+4)(x-6)(x+3)
C=[x²+4x-2x-8][x²+3x-6x-18]
C=[x²+2x-8][x²+3x-18]
C= x^{4} +3x³-18x²+2x³+6x²-36x
C= x^{4} +5x³-12x²-36x
Meilleure réponse !
2013-12-14T00:01:38+01:00
A= -6 (2x-3) (5-4x)
A= -6 (10x - 8x ²- 15 +12x )
A= -6 ( -8x²+ 22x -15)
A= 48² - 132x +90
A= 48 * 48 - 132 x + 90 
A= 16 * 16 -  44 x + 30  ( en simplifiant par 3)
A = 16² - 44 x + 30

B = (x - 6) (-2x+1) (3x-4)
B = (x - 6) (-6x² + 11x -4 )
B = -6 x³ + 11x²- 4x + 36x ²- 66x + 24
B = -6 x³ + 46x² - 70x +24 ( en simplifiant par 2 )
B = -3 x³ + 23x² - 35x + 12

C = (x-2) (x+4) (x-6) (x+3)
C = ( x² + 4x - 2x - 8 ) ( x² + 3x - 6x -18 )
C = ( x² + 2x - 8 ) ( x² + 3x - 18 )
C = x^4 + 3x³ - 18x² + 2x³ + 6x² - 36x - 8 x² - 24x +144 
C = x^4 + 5x³ - 20x² - 60x + 144